Muslim Brotherhood and terrorism : facts and evidence - Markaz al-Imt lil-Dirt wa-al-Buth al-Istiryah (Abu Dhabi : Emirates Center for Strategic Studies and Research, 2017)
"This book reviews facts and evidence based on the Muslim Brotherhood's own literature, the thoughts of its leaders and its notable figures that prove the group's connections with extremist thought and violent and terrorist acts, whose impact has gone beyond the Arab region to affect all corners of the globe. Moreover, this book seeks to reveal the truth that the Muslim Brotherhood has always sought to hide regarding its responsibility for spreading extremism and terrorism under the pretext and slogans of moderation and claims of grievances." --Page [4] of cover.
Introduction -- Foundations of violence and terrorism in Muslim Brotherhood thought -- Muslim Brotherhood : a history of terrorist practices -- Muslim Brotherhood : the origin of all terrorist groups -- Bibliography.
Includes bibliographical references: pages 87-90.
Keywords: Ikhwn al-Muslimn.; Ikhwn al-Muslimn.; Terrorist organizations; Terrorism; Terrorism; Terrorist organizations